2018
DOI: 10.2147/dddt.s166525
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV/lncRNA-TUG1/TRAF5 signaling pathway participates in podocyte apoptosis of diabetic nephropathy rats

Abstract: ObjectiveThis study aims to figure out the mechanism of astragaloside IV (AS-IV) in the protection of podocyte apoptosis in diabetic nephropathy (DN) rats.Materials and methodsStreptozotocin (STZ) was used to induce diabetes in rats, and the diabetic rats were treated with 5 mg/kg/d of AS-IV for 12 weeks. Albuminuria level, relative TUG1 and TRAF5 levels, and TRAF5 and cleaved-caspase-3 protein levels were examined by ELISA, quantitative reverse transcription (qRT)-PCR, and Western blot analyses, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 32 publications
(31 reference statements)
1
62
0
2
Order By: Relevance
“…LncRNA GAS5 is also a proapoptotic lncRNA, in which GAS5 promoted the human renal tubular epithelial cells apoptosis under high glucose environment (Lv et al, 2019) In contrast to that, lncRNA GM15645 expression was low in DN mice and podocyte cells upon stimulation of high glucose, and this lncRNA acts opposite to lncRNA GM5524 in the regulation of podocyte cells apoptosis and autophagy (Feng et al, 2018). Similar to the anti-apoptotic effects of GM15645, lncRNA Taurine upregulated-1 (TUG-1), was downregulated in the DN and hyperglycemic condition, with evidence of renal damage and loss of podocyte cells in DN patients and animal model (Lei et al, 2018;Shen et al, 2019). Loss of TUG-1 expression reduces peroxisome proliferator-activated receptor gamma coactivator 1-alpha (Ppargc1a) expression, as TUG-1 binds to the promoter region of the Ppargc1a gene to increase its expression (Long et al, 2016).…”
Section: Lncrnas In Autophagy and Apoptosismentioning
confidence: 98%
See 2 more Smart Citations
“…LncRNA GAS5 is also a proapoptotic lncRNA, in which GAS5 promoted the human renal tubular epithelial cells apoptosis under high glucose environment (Lv et al, 2019) In contrast to that, lncRNA GM15645 expression was low in DN mice and podocyte cells upon stimulation of high glucose, and this lncRNA acts opposite to lncRNA GM5524 in the regulation of podocyte cells apoptosis and autophagy (Feng et al, 2018). Similar to the anti-apoptotic effects of GM15645, lncRNA Taurine upregulated-1 (TUG-1), was downregulated in the DN and hyperglycemic condition, with evidence of renal damage and loss of podocyte cells in DN patients and animal model (Lei et al, 2018;Shen et al, 2019). Loss of TUG-1 expression reduces peroxisome proliferator-activated receptor gamma coactivator 1-alpha (Ppargc1a) expression, as TUG-1 binds to the promoter region of the Ppargc1a gene to increase its expression (Long et al, 2016).…”
Section: Lncrnas In Autophagy and Apoptosismentioning
confidence: 98%
“…Loss of TUG-1 expression reduces peroxisome proliferator-activated receptor gamma coactivator 1-alpha (Ppargc1a) expression, as TUG-1 binds to the promoter region of the Ppargc1a gene to increase its expression (Long et al, 2016). Consequently, loss of TUG-1 expression increases the tumor necrosis factor receptorassociated factor 5 (Traf5) expression and stimulates the podocyte cell death (Lei et al, 2018). Restoration of TUG-1 expression inhibits Traf5 protein production, not its mRNAs expression, and ameliorates podocyte cell survival (Lei et al, 2018).…”
Section: Lncrnas In Autophagy and Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that [8], NHX1 can convert the phosphate group into GTP in GDP, which activates Ras. NHX1 protein is expressed in the glomeruli and renal tubules of human kidneys [9]. In 2016, a large-scale exome analysis showed that NHX1 regulates kidney development and function [10].…”
Section: Discussionmentioning
confidence: 99%
“…Reducing MALAT1 levels can improve renal functions after duodenal-jejunal bypass in diabetic rats [79]. Increasing expression of lncRNA TUG1 (taurine upregulated gene 1) can attenuate podocyte apoptosis, alleviate extracellular matrix accumulation and protect diabetic rats from DN [80,81]. Besides, TUG1 was also reported to regulate mitochondrial bioenergetics in DN [82].…”
Section: Diabetic Nephropathymentioning
confidence: 99%